Pengaruh Return on Investment dan Struktur Biaya terhadap Tingkat Kembalian Ekonomi - Harjanti Widiastuti (Journal of Accounting and Investment, 2003)
This study aims to examine the economic validity of Return on Investment (ROI) and cost structure related to the level of economic returns as measured by Tobin's q. This research was conducted at pemanufakturan company listed on the Jakarta Stock Exchange (JSX). Data were analyzed using ordinary least squares (OLS). Results of the study provide empirical evidence that the rate of change of accounting (accounting return on investment or ROI) associated with the level of economic return (economic rate of return) or economic rents, although with low correlation coefficient (below 0.5). This research can confirm the research Jacobson (1987) and Landsman and Shapiro (1995).